2015
DOI: 10.4236/ojapps.2015.54015
|View full text |Cite
|
Sign up to set email alerts
|

Concept of Spinsonde for Multi-Cycle Measurement of Vertical Wind Profile of Tropical Cyclones

Abstract: Tropical cyclones and cyclogenesis are active areas of research. Chute-operated dropsondes jointly developed by NASA and NCAR are capable of acquiring high resolution vertical wind profile of tropical cyclones. This paper proposes a chute-free vertical retardation technique (termed as spinsonde) that can accurately measure vertical wind profile. Unlike the expendable dropsondes, the spinsonde allows multi-cycle measurement to be performed within a single flight. Proof of principle is demonstrated using the Rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…They typically contain a GPS receiver, along with other sensors to record atmospheric profiles [13]. Measurement of vertical wind profile using chutefree spinsonde technique has recently been proposed, and simulations indicate that the method is promising [14]. Eliminating the bulky chute will increase payload capacity and more importantly, enable the VWP measurement to be repeated multiple time per flight [14].…”
Section: Introductionmentioning
confidence: 99%
“…They typically contain a GPS receiver, along with other sensors to record atmospheric profiles [13]. Measurement of vertical wind profile using chutefree spinsonde technique has recently been proposed, and simulations indicate that the method is promising [14]. Eliminating the bulky chute will increase payload capacity and more importantly, enable the VWP measurement to be repeated multiple time per flight [14].…”
Section: Introductionmentioning
confidence: 99%
“…This result also suggested that the uncertainty did not appear to be adversely affected by the variation in wind intensity, which was similar to the characteristic of the spinsonde. Reference [6] reported that the measurement uncertainty of the spinsonde remained within ±5 km·h . The rotosonde maneuver was terminated at altitude below 100 m above ground level (AGL) to avoid the trees and power to the main rotor was resumed.…”
Section: Characterization Of the Rotosonde Performancementioning
confidence: 99%
“…Following [6], the measured atmospheric wind speed would be equated with the ground speed of the helicopter, which in turn would be equivalent to the speed measurement acquired by the onboard GPS receiver unit if it were in real field testing. The rotosonde maneuver was initiated while the helicopter was in cruising flight.…”
Section: Characterization Of the Rotosonde Performancementioning
confidence: 99%
See 2 more Smart Citations